(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the philosophical concept of Aziz Abdykasymovich Saliev (1925–2012), presented in his fundamental work “The Doctrine of Thought”. The study analyzes the structure and key categories of the doctrine, including the ontology of thought, its systemic nature, its relationship with language, creativity, and the social context. Special attention is given to Saliev’s four philosophical accents: systematicity, imagery, historicity, and methodological synthesis. The paper provides a comparative analysis of parallels and differences between Saliev’s ideas and the approaches of Hegel, Marx, and Heidegger. It concludes that Saliev’s doctrine of thought is an original concept that combines national cultural foundations with universal philosophical traditions, and that it is significant both for the development of Kyrgyz philosophy and for the global philosophical discourse.